A Framework for Hazard Analysis of Safety-Critical Computer Controlled Systems - Kumar, Kadupukotla Satish; Ramaiah, Panchumarthy Seetha (IJRDO -Journal of Computer Science Engineering, 2016)
Safety-Critical Computer Controlled Systems(SCCCS) are those systems whose failure couldresult in loss of life, significant propertydamage, or damage to the environment. Thereare many well known examples in applicationareas such as medical devices, aircraft flightcontrol, weapons, and nuclear systems. Thesesystems consist of a set of functional elements,controlled by embedded processors that togetherachieve a common objective. Most softwarerelatedaccidents occurred in SCCCS byexecuting flawed programming and instructions.The research literature currently lacks anappropriate safety analysis and is fragmentedamong activities. The aim of this paper is toreduce the probability of unsafe systemconditions using a variety of management,organization and technical measures. Theapproach begins with conducting three differenttypes of hazard analysis techniques to SCCCSsuch as Software Failure Mode and EffectsAnalysis (SFMEA), Software Fault TreeAnalysis (SFTA) and Systems-Theoretic ProcessAnalysis (STPA). In this paper, the applicationof systems-theoretic approach is implemented onBall Position Control System (BPCS) andperformed the comparison between traditionalmethods and systemic methods for analysis anddesign. The proposed systems-theoreticapproach can be applied to SCCCS in diversesectors to identify and control the identifiedhazards. There is clear value in developing asystems-theoretic approach to safety analysis inSCCCS. Development of a SCCCS based onour proposed software safety approachsignificantly enhanced the safe operation of theoverall system.